Chemical constituents of Chirita drakei Burtt collected in Ha Long Bay, Quang Ninh province, Viet Nam. Part 2. Compounds isolated from the n-butanol extract - Hoang Anh, Nguyen Thi; Tuan, Nguyen Van; Quan, Tran Duc; Thien, Dao Duc; Tam, Nguyen Thanh; Thuy, Trinh Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2017)
Four phenol glycosides together with cannabiside B were isolated from the n-butanol extract of the aerial part of Chirita drakei Burtt collected in islands, on mountain slopes of Ha Long bay, Quang Ninh province. Their structures have been elucidated by mass, NMR spectroscopy and comparison with published data. Compounds 4 and 5 were obtained for the first time from the genera Chirita. Keywords. Chirita drakei, phenylethanoid glycoside, phenol glucoside, α,β-unsaturated g-lactone C-glucoside.